Desain Toko Oleh-Oleh dan Kopitiam Bernuansa Peranakan Sebagai Warisan Budaya - Marcelina Chananta; Freddy Handoko Istanto; Maureen Nuradhi (Universitas Ciputra Surabaya, 2015)
Cahaya’s retail an kopitiam is a design project of the interior and achitecture (building’s volume and facade). The retail store located in the first floor sells variety of merchandise and souvenirs.The store sell products of many kinds of food, clothings,and souvenirs made by the locals. Kopi tiam serves main course and light meal with strais chinese indonesian’s cuisine specialties. The target consumer of the retail and kopitiam comes from tourist and local people, that needs to shop for local merchandise and souvenirs. Basedon that facts and client’s wants the write than apply design’s concept that suits the brief, the concept is Explore Cahaya’s House of Heritage”. This concept offers warm welcome to the customer and brings out the historical value of Cahaya as retail that wase stablished since 1907 in Makassar by the ancestors.